Implementation of Music, Arts, Physical Education and Health (MAPEH) Program and Challenges Encountered: Basis for a Proposed Action Plan - Dulay, Malvin Quiles (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study used the descriptive-survey method of research because it was most appropriate to use in determining the status of the MAPEH program in terms of its implementation and challenges. It used a survey-questionnaire as the main instrument to gather the data needed in the study. It involved 22 school administrators and 70 MAPEH teachers sourced from nine public junior high schools who served as respondents in the study. The data gathered were statistically treated using weighted mean, t-test, frequency count and ranking. The study generated the following findings: (1). The MAPEH program was implemented to a high extent in terms of the program’s objectives, curriculum, learning resources, teachers’ qualification, and competency, administrative support, funding, and community partnership. (2). There was no significant difference between the assessment of the two groups of respondents in the implementation of MAPEH program in terms of the aforementioned aspects. (3) The top five challenges encountered by the two groups of respondents in the implementation of the MAPEH program were: a) Fund for MAPEH program is not enough to finance its needs, b) Facilities for Music, Arts, P.E. and Health Education are not adequate c) Not all MAPEH teachers are competent in teaching all the components of the subject, d) Students’ engagement in MAPEH activities was limited in this pandemic time and e) Online instruction for MAPEH activities was difficult to carry out. (4) An action plan was proposed based on the result of the study.